The Role of Appropriate Technology in Sustainable Development Design - Sonjaya, Yaya; Noch, Muhamad Yamin; Sutisna, Entis (Advances in Community Services Research, 2024)
Purpose: This study investigates the role of appropriate technology in sustainable development, focusing on its economic, environmental, and social dimensions. The purpose is to examine how appropriate technology can be effectively integrated into sustainable development design. Research Design and Methodology: A qualitative methodology was used, involving an extensive literature review of recent studies on appropriate technology. The research categorized findings into economic viability, environmental sustainability, and social inclusivity, and conducted a thematic analysis to synthesize these dimensions. Findings and Discussion: Findings reveal that appropriate technology offers significant economic benefits by reducing costs and fostering local entrepreneurship, enhances environmental sustainability through renewable resources and waste reduction, and promotes social inclusivity by engaging communities in the design process. The discussion highlights that appropriate technology can drive sustainable development by providing affordable, environmentally friendly, and socially equitable solutions. Implications: Implications suggest that successful integration requires innovative financing, supportive policies, and community engagement. This research provides a comprehensive framework for advancing the application of appropriate technology in sustainable development, offering insights for policymakers and practitioners